Mild phenotype in Molybdenum cofactor deficiency: A new patient and review of the literature. Issue 6 (21st March 2019) - Scelsa, Barbara; Gasperini, Serena; Righini, Andrea; Iascone, Maria; Brazzoduro, Valeria G.; Veggiotti, Pierangelo
Abstract: Background: Molybdenum cofactor deficiency (MoCD) is a rare autosomal‐recessive disorder that results in the combined deficiency of molybdenum‐dependent enzymes. Four different genes are involved in Molybdenum cofactor biosynthesis: MOCS1, MOCS2, MOCS3, and GEPH . The classical form manifests in the neonatal period with severe encephalopathy, including intractable seizures, MRI changes that resemble hypoxic‐ischemic injury, microcephaly, and early death. To date, an atypical phenotype with late‐onset has been reported in the literature in 13 patients. Methods: We describe a late‐onset and a relatively mild phenotype in a patient with MOCS2 homozygous mutation. Results: Pyramidal and extrapyramidal signs are recognized in those patients, often exacerbated by intercurrent illness. Expressive language is usually compromised. Neurological deterioration is possible even in adulthood, probably due to accumulation of sulfite with time. Conclusion: Sulfite inhibition of mitochondrial metabolism could be responsible for the ischemic lesions described in patients with MoCD or alternatively could predispose the brain to suffer an ischemic damage through the action of other insults, for instance intercurrent illness. It is possible that sulfite accumulation together with other external triggers, can lead to neurological deterioration even in adulthood. The role of other factors involved in clinical expression should be investigated to establish the reason for phenotypic variability in patients with the same mutation. Abstract : Molybdenum cofactor deficiency (MoCD) is a rare autosomal‐recessive disorder that results in the combined deficiency of molybdenum‐dependent enzymes. To date, an atypical phenotype with late‐onset has been reported in the literature in 13 patients. We describe a late‐onset and a relatively mild phenotype in a patient with MOCS2 homozygous mutation. Pyramidal and extrapyramidal signs are recognized in those patients, often exacerbated by intercurrent illnesses. Neurological deterioration is possible even in adulthood, probably due to accumulation of sulfite with time.